Cutting Edge of Alzheimer’s Disease Research: Literature Review for the Changes in Brain Function in the Prodromal Stages of Alzheimer’s Disease - Ryan, Tristram A. J. (Trinity Student Medical Journal, 2020)
Alzheimer’s disease (AD) is a complex neurodegenerative disorder that is estimated to affect 44 million people worldwide, and the global incidence of AD is expected to triple by 2050, thus making it a major current topic with the ageing global population. Whilst symptoms generally present late in life, many details of AD pathogenesis remain unclear. Current thinking suggests cognitive tasks are performed not by individual brain regions working in isolation, but by functionally connected networks. Hence AD research is turning to the study of large-scale networks such as the Default Mode Network (DMN), primarily involved in processing memories, which is observed as the first locus of the disease. Consequently, there is a paradigm shift towards focused research on earlier stages. Mild cognitive impairment (MCI) is a prodromal stage of AD, displaying cognitive deficit but neither marked functional impairment nor satisfying established clinical criteria for dementia or probable AD. MCI subjects are at risk of AD but otherwise are unimpaired in daily living. It is noted that if MCI is a portal into potential AD, the field must work towards a better understanding of the MCI stage and emerging therapies for MCI. Thus, there is a clear need to make use of the data freely available from the ongoing Alzheimer’s Disease Neuroimaging Initiative (ADNI) to investigate changes in network function in the prodromal stages of AD with the ambition of gaining a better understanding of the MCI stage of AD.